Machine learning uncovers independently regulated modules in the Bacillus subtilis transcriptome - Kevin Rychel (Nature Portfolio, 2020)
The systems-level regulatory structure underlying gene expression in bacteria can be inferred using machine learning algorithms. Here we show this structure for Bacillus subtilis, present five hypotheses gleaned from it, and analyse the process of sporulation from its perspective.